Penyuluhan Kesehatan Tentang Bahaya Pergaulan Bebas pada Remaja di Tarusan Kamang: Penyuluhan Kesehatan Tentang Bahaya Pergaulan Bebas pada Remaja di Tarusan Kamang - Dian Sari; Meka Melani Sari; Amelya Permata Sari (Ruang Ide Publisher, 2026)
Adolescents are an age group vulnerable to risky behavior, including promiscuity, which impacts reproductive health. National data over the past five years shows an increase in cases of sexually transmitted infections, unwanted pregnancies, and mental health disorders among adolescents. The lack of comprehensive education and safe discussion spaces are the main factors that cause these behaviors. This community service activity aims to increase adolescent knowledge and awareness regarding the dangers of promiscuity in adolescents. The activity was carried out through health counseling to adolescents using interactive lectures, discussions, and educational media. Evaluation was carried out using pretest and posttest questionnaires to measure changes in participants' knowledge levels. The results of the activity showed an average increase of 22% in adolescents’ knowledge. Health education is effective in increasing adolescent knowledge and understanding regarding the dangers of promiscuity. Similar activities with varied themes need to be carried out routinely and continuously by coordinating with local health teams and integrating with school programs so that adolescents grow healthily.